5i-1=14(i)

Simple and best practice solution for 5i-1=14(i) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5i-1=14(i) equation:


Simplifying
5i + -1 = 14(i)

Reorder the terms:
-1 + 5i = 14(i)

Solving
-1 + 5i = 14i

Solving for variable 'i'.

Move all terms containing i to the left, all other terms to the right.

Add '-14i' to each side of the equation.
-1 + 5i + -14i = 14i + -14i

Combine like terms: 5i + -14i = -9i
-1 + -9i = 14i + -14i

Combine like terms: 14i + -14i = 0
-1 + -9i = 0

Add '1' to each side of the equation.
-1 + 1 + -9i = 0 + 1

Combine like terms: -1 + 1 = 0
0 + -9i = 0 + 1
-9i = 0 + 1

Combine like terms: 0 + 1 = 1
-9i = 1

Divide each side by '-9'.
i = -0.1111111111

Simplifying
i = -0.1111111111

See similar equations:

| 2(6.4-0.5n)= | | 22-5x=(-28) | | 0.3(6+y)-0.3y=1.8 | | (a-b)+(3a+2b)= | | 18x+22=-14 | | q/9=32 | | x+15=-4x+4 | | 44=-52x | | 24=(x+4)+10(x-1)+4x | | -28-7=4 | | f(g(x))=2x^2+11x-6 | | 8-8=16x+13x | | -28-7= | | 5(v-3)+4(2v-1)= | | 125x-12=3500 | | -8(m+7)-9(m+15)=-14m-4+14m | | 4(x-3)=1(7x+28)+3 | | 5i-1=14Xi | | 9(x+4)-5=39-6x-8+15x | | -4(4x-3)-(6x+4)= | | a^2+ab+b^2=0 | | X-4-3x=-3x-3-1 | | -4(9a-b)+3(5a+2b)=0 | | 2x+4(2x-4)=-6 | | 2x+(-8)=-2 | | x^2+6x+5x+4+5=69 | | 107=-2n+5(1+6n) | | 7x-5-72=0 | | 2g+3(-4+5g)=1-g | | -4(3x+2)=(6x-6) | | 5i-1=14i | | 2t^2-9t+13=0 |

Equations solver categories